Implementation of E-Commerce for Andika Jeans with PHP, MySQL, and SDLC for Web-based Applications - Handayani, Indah Tri (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The website has information about the product's name, price, and specifications, which aims to make it easier for customers to choose the product they want to buy. This website is exclusively for men's jeans. This men's jeans E-Commerce Website contains information about products for men's needs. Andika Jeans previously used conventional methods, where customers had to come to the store to see the product. With these problems, the Andika Jeans website was created. The method used in this writing is SWLDC, which has several stages: analysis, design, implementation, and trial. The conclusion that can be drawn from this website is that it aims to get information about the available products so that visitors can easily choose products that meet their needs. This website has been hosted so that customers can access it and can also place and confirm orders. This website has been tested in several browsers and devices, and the results of this website function very well; this website can be accessed via http://widi-system.co/andikajeans/.